Cytological and cytomorphometric study of exfoliated cells of the oral mucosa in diabetic patients - Kavitha Gaddikeri; Mohammed Abidullah; Deepak Bhorgonde (Wolters Kluwer Medknow Publications, 2020)
Background: Systemic disorder like diabetes mellitus is on the rise in developing countries like India and in many parts of the world. Early diagnosis of this disease will help to prevent the complications due to uncontrolled diabetes mellitus. Dentist helps in the early diagnosis of this disease as patients manifest several oral manifestations. Aims and Objectives: The aim of this study was to study the cytological and cytomorphometric changes of exfoliated cells of oral mucosa in diabetic patients. Materials and Methods: Thirty diabetic patients and 15 healthy controls were included in the study. From the buccal mucosa, smears were collected and Papanicolaou stain was used for staining. Cytological and cytomorphometric study was carried out. The cell diameter and nuclear diameter were measured on these smears and were compared with the control group with the help of "unpaired Student t test."Results: Buccal mucosa exfoliated cells' mean nuclear diameter of diabetic group and control group was 11.198 and 9.494 µm, respectively and the difference was highly significant. Conclusion: Our study suggests significant cellular changes in the diabetic patients, which may aid us in early detection of diabetes.